Field gamma dose-rate measurement with a NaI(Tl) detector: re-evaluation of the "threshold" technique - Mercier, N.; Falguères, C. (Ancient TL, 2007)
Radiation detectors, like doped NaI, are commonly used in the field for the determination of gamma dose-rates. In most cases, and even though these systems generally allow one to record the full gamma spectrum between 0 to around 3 MeV, this dose-rate is computed from the count rates recorded in a limited number of "windows" (Aitken, 1985). With this technique, only a small part of the spectrum is therefore exploited. Nevertheless, an alternative approach - the "threshold" technique – known for more than 30 years, can easily be used with the same detection system. In this paper, we make a re-evaluation of this technique and discuss its limits and advantages.